Environmental gradients of Nypa fruticans productivity and benthic macrofaunal assemblages in an acidic peat coastal ecosystem, Eastern Sumatra, Indonesia - HANAN AZ ZAHRA SYAFINA; AGUS HARTOKO; PUJIONO WAHYU PURNOMO (Society for Indonesian Biodiversity, 2025)
Abstract. Syafina HAZ, Hartoko A, Purnomo PW. 2025. Environmental gradients of Nypa fruticans productivity and benthic macrofaunal assemblages in an acidic peat coastal ecosystem, Eastern Sumatra, Indonesia. Biodiversitas 26: 6212-6223. Nypa fruticans is a significant palm species found along tropical peat-fringed coasts; however, there is limited understanding of how its productivity and benthic fauna respond to hydrochemical gradients in acidic peat systems in this region. This study aimed to quantify the relationships of salinity and soil pH with N. fruticans aboveground biomass (AGB), carbon stocks, leaf chlorophyll, and benthic macrofauna along an estuarine–coastal gradient on an acidic peat coast in eastern Sumatra, Indonesia. We hypothesised that Nypa productivity and benthic richness and diversity would be highest in low-salinity, acidic estuarine plots and would decline towards saline, near-neutral coastal plots. We established 30 independent 10 × 10 m plots (10 per zone: estuarine, transitional, and coastal) and measured AGB (dry mass), carbon (C = 0.5 × AGB), leaf chlorophyll content, salinity, and soil pH. Benthic macrofauna were sampled using three 25 × 25 cm quadrats per plot, and diversity indices were calculated from quadrat and plot-level abundances. Differences among zones and their associations with environmental variables were assessed using ANOVA, non-parametric tests, correlation analysis, and PCA. AGB decreased from 45.9 ± 4.2 t ha-¹ in the estuarine zone to 3.1 ± 1.7 t ha-¹ and 1.1 ± 0.5 t ha-¹ in the transitional and coastal zones (F₂,₂₇ = 41.52, p < 0.001), with proportional reductions in the carbon stocks. Chlorophyll content was correlated with AGB (r = 0.84, p < 0.001), supporting its use as a measure of vigour. Benthic diversity (Shannon H′) declined from 1.450 in estuarine plots to 1.073 in coastal plots, and total benthic abundance decreased seaward, parallel to the declining Nypa productivity. Over this gradient, salinity increased from 0-1.4‰ to 9-10‰, and soil pH shifted from acidic ( 2.35) to near-neutral ( 7.0). Biotic variables were negatively associated with the salinity–pH axis in the PCA, indicating that hydrochemical gradients jointly structured the vegetation and benthos. This first gradient-based study of Indonesia’s acidic peat coasts quantifies Nypa productivity and benthic macrofauna along a salinity–pH gradient, providing a baseline for future multi-season investigations.